Expression Analysis of TCP Transcription Factor Family in Autopolyploids of Chrysanthemum nankingense - Yu, Zhongyu; Tian, Chang; Guan, Yunxiao; He, Jun; Wang, Zhenxing; Wang, Likai; Lin, Sisi; Guan, Zhiyong; Fang, Weimin; Chen, Sumei; Zhang, Fei; Jiang, Jiafu; et al. (Frontiers in Plant Science, 2022)
Autopolyploids often exhibit plant characteristics different from their diploid ancestors and are frequently associated with altered genes expression controlling growth and development. TCP is a unique transcription factor family in plants that is closely related to plant growth and development. Based on transcriptome sequencing of Chrysanthemum nankingense, 23 full-length TCP genes were cloned. The expression of CnTCP9 was most variable in tetraploids, at least threefold greater than diploids. Due to the lack of a C. nankingense transgenic system, we overexpressed CnTCP9 in Arabidopsis thaliana (Col-0) and Chrysanthemum morifolium. Overexpression of CnTCP9 caused enlargement of leaves in A. thaliana and petals in C. morifolium, and the expression of genes downstream of the GA pathway in C. morifolium were increased. Our results suggest that autopoly-ploidization of C. nankingense led to differential expression of TCP family genes, thereby affecting plant characteristics by the GA pathway. This study improves the understanding of enlarged plant size after autopolyploidization.